Ten roles for teacher leaders - Harrison, Cindy; Killion, Joellen (Educational Leadership, 2007)
Teacher leaders assume a wide range of roles to support school and student success. Harrison and Killion describe 10 roles that teacher leaders can fulfill in their schools. As resource providers, they provide materials to help their colleagues. Instructional specialists help colleagues with instructional strategies, and curriculum specialists ensure that the adopted curriculum is consistently implemented. Teachers can also coteach and observe in colleagues' classrooms or mentor new teachers. Planning professional learning opportunities and serving on committees are also important roles. Some teachers also encourage colleagues to analyze and use data more effectively, learn new things, or change the status quo. The variety of formal and informal opportunities these roles encompass means that any teacher can be a leader.